2016
DOI: 10.1371/journal.pone.0166968
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Round Hyporeflectivities in Geographic Atrophy

Abstract: PurposeIn geographic atrophy (GA), choroidal vessels typically appear on structural optical coherence tomography (OCT) as hyperreflective round areas with highly reflective borders. We observed that some GA eyes show choroidal round hyporeflectivities with highly reflective borders beneath the atrophy, and futher investigated the charcteristcs by comparing structural OCT, indocyanine green angiography (ICGA) and OCT angiography (OCT-A).MethodsRound hyporeflectivities were individuated from a pool of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Focal internal reflective feature s may represent crystallizations (Figure 2G). An especially intriguing cavern characteristic is a prominent and consistent posterior tail of hypertransmission, which differentiates caverns from choroidal vessels, “round hyporeflectivities” considered cavern precursors, 8 and fluid-filled cysts or cavitations. Tails may relate to lower absorption of incoming light by lipid than by surrounding tissue (Supplementary Information, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal internal reflective feature s may represent crystallizations (Figure 2G). An especially intriguing cavern characteristic is a prominent and consistent posterior tail of hypertransmission, which differentiates caverns from choroidal vessels, “round hyporeflectivities” considered cavern precursors, 8 and fluid-filled cysts or cavitations. Tails may relate to lower absorption of incoming light by lipid than by surrounding tissue (Supplementary Information, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To explain the appearance of caverns, the authors suggested that similar changes occur in the larger vessels of the Sattler and Haller layers, with the internal punctate hyperreflectivity corresponding to cells. These investigators subsequently described choroidal round hyporeflectivities, 8 which were similar in size to choroidal caverns, yet distinct due to hyperreflective borders and a consistent round shape, and suggested these as non-or hypo-perfused vessels, single large cells, or cavern precursors. Among the explanations for choroidal round hyporeflectivities of SD-OCT, the authors also included Friedman lipid globules, citing a preliminarily presented survey of these features.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, analogies could be seen between the changes of the choriocapillaris and choroid caused by SC and geographic atrophy. These included a focal flow impairment and rarefaction in the choriocapillaris beneath the area of the atrophic lesions, which is argued to represent non-perfused or hypo-perfused choroidal vessels with non-detectable flow in the literature [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, analogies could be seen between the changes of the choriocapillaris and choroid caused by SC and geographic atrophy. These included a focal flow impairment and rarefaction in the choriocapillaris beneath the area of the atrophic lesions, which is argued to represent non-perfused or hypo-perfused choroidal vessels with non-detectable flow in the literature [27,28,29].…”
Section: Discussionmentioning
confidence: 99%